ANTIBACTERIAL AND ANTICANCER POTENTIAL OF SILVER NANOPARTICLES SYNTHESIZED USING GALLIC ACID IN BENTONITE/STARCH BIO-NANOCOMPOSITES - Thapliyal, Anupama; Chandra, Amrish (International Journal of Applied Pharmaceutics, 2018)
Objective: To optimize and synthesize eco-friendly and low-cost silver nanoparticles (AgNPs) by using gallic acid (GA) reducing agent in bentonite/starch bio-nanocomposites (BNCs) for oral use and to evaluate its antibacterial and anticancer efficacy. Methods: An artificial neural network (ANN) model was employed for the optimization and evaluate the effect of the formulation variables on the entrapment efficiency (EE) of AgNPs. The synthesized AgNPs in BNCs were characterized using UV-vis spectroscopy, energy dispersive X-ray spectroscopy (EDXA), dynamic light scattering (DLS), scanning electron microscopy (SEM), zeta potential and fourier transform infrared spectroscopy (FTIR). Elemental ion analysis was carried out using inductively coupled plasma mass spectrometry (ICP-MS). Drug release study was carried out. The antimicrobial efficacy determined by agar well diffusion method. In vitro anticancer efficacy of AgNPs in breast cancer cell line (MCF-7) by MTT assay was performed. Results: The formation of AgNPs was confirmed by UV-vis absorbance peak shown at 412 nm. XRD spectrum has indicated the face-centered cubic structure of the synthesized AgNPs. SEM and DLS measurements showed spherical nanoparticles with a mean size of 68.06±0.2 nm. The negative surface zeta potential with-32±0.25 mV has indicated colloidal stability of nanoparticles. FTIR spectra confirmed no interaction observed between drug and excipients. AgNPs showed significant EE with 80±0.25%. The synthesized AgNPs in BNCs is a potential candidate for inhibiting the growth of pathogenic bacteria and showed significant cytotoxicity against MCF-7 cancer cell line with IC50 of 160±0.014μg/ml. Conclusion: The present research confirms that the green synthesized AgNPs in BNCs can be a promising antibacterial and anticancer agent regarding stability, low cost and easy preparation.